Efficient gene and siRNA delivery with cationic polyphosphoramide with amino moieties in the main chain. Issue 62 (8th July 2015) - Xu, Wanfu; Wang, Yaodong; Li, Songyu; Ke, Zhiyong; Yan, Yichen; Li, Shao; Xing, Zhe; Wang, Chunxia; Zeng, Fangyin; Liu, Ruiyuan; Deng, Fan
<x xml:space="preserve">Abstract</x> A novel cation polyphosphoramide with amino moieties in the main chain was synthesized, which can be used as efficient carriers for plasmid and siRNA.